Policy styles and policy-making: exploring the linkages - Howlett, Michael; Tosun, Jale (Routledge, 2019)
Policy styles : a new approach / Michael Howlett and Jale Tosun -- Policy styles in the United Kingdom : a majoritarian UK vs devolved consensus democracies? / Paul Cairney -- Policy styles in Germany : still searching for the rationalist consensus? / Reimut Zohlnhöfer and Jale Tosun -- The scholar-official policy nexus and Confucian policy styles in South Korea / M. Jae Moon and Chang-ho Hwang -- Policy styles in Mexico : still muddling through centralized bureaucracy, not yet through the democratic transition / Raul Pacheco-Vega -- The co-evolutionary policy style of Brazil : structure and functioning / Eduardo José Grin and Fernando Luiz Abrucio -- Over-promising and under-delivering : the Canadian policy style of punctuated gradualism / Michael Howlett and Andrea Migone -- Policy style(s) in Switzerland : under stress / Yannis Papadopoulos and Martino Maggetti -- The American policy style(s) : multiple institutions creating gridlock and opportunities / B. Guy Peters -- Policy styles in China : how to control and motivate bureaucracy / Jiwei Qian -- Policy-making styles in Central Asia : the Soviet legacy and new institutions / Aziz Burkhanov]-- Vietnam : the policy styles of a lame Leviathan / Aurel Croissant -- The national policy-making style of the United Arab Emirates : fusing patron-client networks into modernity / Ahmed Mustafa Elhussein Mansour -- The riven policy style of a post-empire state : the case of Russia / Dmitry Zatsyev -- Singapore's policy style : gradations of developmentalism / Jun Jie Woo -- Policy-making in an electoral autocracy : constitutional reform in Togo / Anja Osei and Hervé Akinocho -- Napoleonic traditions, majoritarianism, and Turkey's statist policy style / H. Tolga Bolukbasi and Ebru Ertugal -- Empirical insights on national policy styles and political regimes / Michael Howlett and Jale Tosun
Includes bibliographical references and index
Keywords: Fallstudiensammlung; Politischer Stil; Politische Planung